Effect of core training with and without yogic practices on body composition variable among women students - R. MEERA; R. MOHANAKRISHNAN (International Journal of Pharma and Bio Sciences, 2018)
The present study attempted to examine the effect of core training session with and without yogic practices on body composition variable among women students (age 18 ± 3 years). A random selection of 45 female students from the Government Arts and science college Thiruvannamalai in Tamil Nadu, India was carried out. They were grouped into three groups with fifteen members each such as yogic practice group, core strength group and combined yogic core strength training group. The body mass index (BMI) is selected as body composition variable and is tested with height weight ratio calculation in kg/m2. The subjects underwent training for 12 weeks, 4 days a week and 45 to 60 minutes per day with suitable warming up and cooling down exercise. The criterion variable wastested before and soon after subsequent training sessions. A statistical analysis of the obtained data was carried through analysis of covariance. For the evaluation of paired mean difference at the optioned ‘F’ ratio with a significant level at 0.05, the Scheffe’s post hoc test was utilized. After investigation it was observed that, there occurred a significant difference among experimental groups on selected Body composition parameter.